A comparative study of Lichtenstein hernioplasty performed under spinal anaesthesia versus local anaesthesia in treatment of unilateral inguinal hernia - Besra, Siddhabrata; Mohanta, Pradip Kumar; Mallik, Chinmoy; Hussian, Noor Hassan; Biswas, Subikash; Pal, Sabuj; Roy, Debasish (International Surgery Journal, 2019)
Background: Lichtenstein mesh repair technique is widely used throughout the world in inguinal hernia repair. Hernioplasty done under local anaesthesia certainly has some benefits but it is yet to be proven as standard procedure. The aims of this study are to provide the data of a comparative study between Lichtenstein hernioplasties done under local versus spinal anaesthesia as well as add more data in this scenario. Methods: In this non randomized clinical study, 84 patients were selected by calculation of sample size. 42 patients were operated under spinal anaesthesia and another 42 were operated under local anaesthesia. Results: Mean duration of operation was slightly was slightly more in local anaesthesia i.e. 62.5 minutes (SD=17.8) versus 51.1 minutes (SD=21.5) in spinal anaesthesia. At 6 hours, 12 hours and 24 hours postoperative pain was significantly less in local anaesthesia group in comparison to spinal anaesthesia group with p=0.04, p=0.042, p=0.041 respectively. Postoperative complications like urinary retention, hypotension, and headache were more in spinal anaesthesia than in local anaesthesia. Duration of hospital stay was significantly less in local anaesthesia group i.e. 24.5 hours (SD=12.8) in comparison to spinal group 57.1 hours (SD=16.7). Conclusions:The study concludes that in local anaesthesia group, postoperative pain was significantly less and postoperative complications like urinary retention, headache, and hypotension were less evident compared to spinal anaesthesia. Hence the study concludes that local anaesthesia can be used as an alternative of spinal anaesthesia as a standard mode of anaesthesia for Lichtenstein hernioplasty operation.